Assessing climate change impacts in conservation areas and on food systems in the Eastern Cape, South Africa - Effossou, Kablan Antoine; Maphosa, Mandlenkosi; Moyo, Philani (Frontiers in Human Dynamics, 2025)
Biodiversity conservation through protected areas has expanded across sub-Saharan Africa (SSA), and South Africa is no exception. However, the interplay between conservation governance, climate change, and food systems remains understudied in rural contexts. This study examined the interconnections among biodiversity conservation, climate variability, and food systems resilience in Alicedale and Seven Fountains in South Africa’s Eastern Cape province. Using qualitative methods, the research highlighted key challenges such as limited land access, unequal water availability, high unemployment, and climate induced agricultural disruption. Findings revealed that conservation-related restrictions, coupled with unpredictable weather patterns, undermine local food production and access. Participants proposed adaptive strategies, including shared land access, community boreholes, and small-scale farming initiatives. The study concludes that integrating food security concerns into conservation planning, especially in privately owned reserves, require participatory governance models and attention to historical and institutional inequalities. By contributing empirical insights to debates on environmental justice and climate adaptation, this study highlights the need for inclusive, locally responsive natural resource management in marginalised rural areas.